Educational Games and Learning Management Quality as Predictors of Digital Literacy in Mathematics - Ferawati; Refi Nabillah Royadi; Fiqih Hana Saputri (Information Technology Education Journal, 2025)
This study aims to analyze the influence of educational game integration and learning management quality on students’ digital literacy competence in mathematics at SMK Bina Mandiri. The research is motivated by the growing need to strengthen digital literacy skills in technology-based learning, particularly in mathematics, which many students perceive as abstract and challenging. The study adopts a quantitative approach with an explanatory correlational design involving 60 eleventh-grade students. Data were collected using a closed-ended Likert-scale questionnaire (1–5) that had been tested for validity and reliability. Data were analyzed using SPSS with multiple regression, supported by classical assumption tests to ensure the suitability of the model. The results show that all measurement instruments meet the required validity and reliability criteria. The regression model fulfills the assumptions of normality, linearity, multicollinearity, and heteroscedasticity, indicating that the data are appropriate for further analysis. Both partially and simultaneously, educational game integration (X₁) and learning management quality (X₂) positively and significantly affect digital literacy competence in mathematics (Y). The coefficient of determination (R²) of 0.611 indicates that 61.1% of the variance in students’ digital literacy competence is explained by the two independent variables, while the remaining 38.9% is influenced by other factors such as student motivation, technological infrastructure, and the broader learning environment. These findings highlight the importance of structured game-based learning and effective learning management in supporting students’ digital skills. Findings suggest that integrating educational games with strong learning management enhances vocational students’ digital literacy.